Question Word in the Mandarin Language - Yunyu, Xu (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2013)
In an interrogative sentence in Mandarin language, a question word can be placed in the beginning, middle or end of a sentence. Because of the different nation and culture, when a foreign student learns Mandarin, they find it difficult to understand the question words and the position of the question words in that language. Because of that, the writer proposes to explain such problems. This research aims to find out what are the types of question words in Mandarin, and also to explain the function and usage of question words in the Mandarin interrogative sentence. An interrogative sentence is a very important sentence. In Mandarin, the following question words: 谁(shuí) “Who”，在哪里(zài nǎli) “where”, 在哪儿(zài nǎ’er) “where”，为什么(wèi shénme) “why”, 怎么(zěnme) “why”，多少（duō shǎo） “how many”，多久(duō jiǔ) “how long”，什么时候 (shénme shíhòu) “when”，什么(shénme) “what”，做什么(zuò shénme) “why”，干 什么(gàn shénme) “why”，干嘛(gànma) “why” and so on are used to ask “who”, “where”, “what”, “how much”, “when”, “what time”, and “why”. Those words have different functions and usage. Each sentence has a certain structure and word order. A question word can be placed in the beginning, middle, or end of a sentence. When the place is changed, there is a possibility of miscommunication. DOI: https://doi.org/10.24071/llt.2013.160106